Differential gene expression in non-transgenic and transgenic “M.26” apple overexpressing a peach CBF gene during the transition from eco-dormancy to bud break - Artlip, Timothy (Hortic Res, 2019)
The CBF signal pathway is responsible for a significant portion of plant responses to low temperature and freezing. Overexpression of CBF genes in model organisms such as Arabidopsis thaliana enhances abiotic stress tolerance but also reduces growth. In addition to these effects, overexpression of the peach (Prunus persica [L.] Batsch) CBF1 gene in transgenic apple (Malus x domestica Borkh.) line T166 also results in early entry into and late exit from dormancy. Although the regulation of dormancy-induction and dormancy-release occur while the CBF regulon is operative in perennial, woody plants, how overexpression of CBF1 affects these dormancy-related changes in gene expression is incompletely understood. The objective of the present study was to characterize global changes in gene expression in peach CBF1-overexpressing and non-transformed apple bark tissues at different states of dormancy via RNA-seq. RNA-seq bioinformatics data was confirmed by RT-qPCR on a number of genes. Results indicate that the greatest number of significantly differentially expressed genes (DEGs) occurred in April when dormancy release and bud break normally occur but are delayed in Line T166. Genes involved in storage and inactivation of auxin, GA, and cytokinin were generally upregulated in T166 in April, while those for biosynthesis, uptake or signal transduction were generally downregulated in T166. Genes for cell division and cambial growth were also downregulated in T166 relative to the non-transformed line. These data suggest that overexpression of the peach CBF1 gene impacts growth hormone homeostasis and as a result the activation of growth in the spring, and most likely growth cessation in the fall as well.